Screening of mungbean genotypes for tolerance to waterlogging under field condition - Amin, MR; Karim, MA; Khaliq, QA; Islam, MR; Aktar, S (Bangladesh Journal of Agricultural Research, 2015)
Abstract not available Bangladesh J. Agril. Res. 40(3): 513-519, September 2015